Are PMD and electric bicycles as safe to ride as bicycles? - Wong, Brian Yit Cong (Nanyang Technological University, 2022)
This report aims to find out whether PMDs and e-bikes are as safe as conventional bicycles. It seeks to understand the factors that affect safety and to evaluate the performance of different PMDs and e-bikes.